Risk Analysis of the Tsunami Evacuation Infrastructure Based on the ISO 31000 in the Disaster-Prone Coastal Area in Teluk Palu - Asnudin, Andi; Labombang, Mastura; Rizal, Andi; Rivani, Agus; Lioni, Clara Zenicha; Sarungallo, William Arrang (Engineering, Technology & Applied Science Research, 2026)
This study employs a structured risk assessment based on the ISO 31000 framework to evaluate tsunami evacuation infrastructure in Palu Bay, Central Sulawesi. Triggered by the 2018 triple disaster (earthquake, tsunami, and liquefaction) that revealed severe preparedness gaps, this study focused on the vulnerable coastal villages of Tondo and Mamboro. A mixed-methods approach combining field observations, spatial analysis, expert interviews, and Focus Group Discussions (FGDs) was used to identify and analyze risks along 10 evacuation routes and key assembly points. Field observations utilized a checklist containing predetermined variables, including road surface conditions, road width, the presence and clarity of signs, accessibility for people with disabilities, and route connectivity to safe zones. The findings indicated that critical risks, including route blockages, a lack of signs, and inadequate accessibility for people with disabilities, caused dangerous evacuation delays. Spatial analysis using Indonesian Topographic Maps (RBI) and tsunami hazard data overlays revealed that several routes were disconnected from safe zones, and maintenance and inclusive design issues were prevalent. A risk matrix was developed to prioritize interventions, identifying three routes with very high-risk scores (25, 20, and 20) that required immediate action. The study concluded that post-disaster reconstruction in Palu neglected systematic risk assessment and inclusive planning. Recommendations for infrastructure upgrades, regular evacuation drills, improved signage, and integration of geospatial data with real-time monitoring are proposed to address these gaps. By applying the ISO 31000 standard, this study provides a replicable model for enhancing evacuation infrastructure and fostering community resilience in other disaster-prone coastal areas.